2018
DOI: 10.1016/j.carres.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of protected glucose derivatives from levoglucosan by development of common carbohydrate protecting group reactions under continuous flow conditions

Abstract: Common carbohydrate protecting group reactions under continuous flow processes are reported in the context of producing partially-protected glucose building blocks from levoglucosan. Benzyl ether protection was demonstrated without the use of NaH using barium oxide, which, however, pointed to the need for forms of this catalyst not as susceptible to close packing under flow. Acylation conditions were developed under continuous flow in acetonitrile and avoiding pyridine. Ring-opening the derivatized levoglucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Limited examples of the regioselective derivatization of OH groups in levoglucosan include enzymatic acylation 53 and continuous-flow benzylation over a BaO catalyst. 54 However, the products of these systems are not useful as substrates for reductive conversions. Deoxydehydration (DODH) and double-hydrodeoxygenation reactions, which have been recently attracting much attention in the reductive conversion of sugar-derived compounds and are explained later, cannot be applied to levoglucosan because both pairs of vicinal OH groups ( i.e.…”
Section: Levoglucosan and Levoglucosenonementioning
confidence: 99%
“…Limited examples of the regioselective derivatization of OH groups in levoglucosan include enzymatic acylation 53 and continuous-flow benzylation over a BaO catalyst. 54 However, the products of these systems are not useful as substrates for reductive conversions. Deoxydehydration (DODH) and double-hydrodeoxygenation reactions, which have been recently attracting much attention in the reductive conversion of sugar-derived compounds and are explained later, cannot be applied to levoglucosan because both pairs of vicinal OH groups ( i.e.…”
Section: Levoglucosan and Levoglucosenonementioning
confidence: 99%
“…[59] Ring-opening of anhydrosugars by alkyl thiols have been performed using BF 3 • Et 2 O [60] or TMSOTf under continuous flow conditions. [61] Functionalized thioarylglycosides have been obtained by various transformations of the primary hydroxy group released in the ring-opening step. [62][63][64] Karban et al reported for example the preparation of deoxyfluorinated thioglycoside donors for the synthesis of original disaccharides and T n antigen analogues.…”
Section: Access To Thioglycosides As Sugar Donorsmentioning
confidence: 99%
“…Other conditions have been also studied including PhSTMS/TMSOTf [56] and PhSH/TsOH [59] . Ring‐opening of anhydrosugars by alkyl thiols have been performed using BF 3 ⋅ Et 2 O [60] or TMSOTf under continuous flow conditions [61] …”
Section: Ring‐opening With S‐nucleophilesmentioning
confidence: 99%
“…3 Levoglucosan is conventionally synthesized from D-glucose by attaching the 6-OH group to the anomeric center to form a second ring structure. 4 The commonly used synthesis route consists of a series of tedious, time consuming and expensive steps involving the protection of (reactive) hydroxyl groups, activation of the anomeric center in the saccharide, and subsequent removal of the protecting groups. 5 Without the use of protecting hydroxyl groups, it is nearly impossible to convert glucose into a 1,6 anhydrosugar derivative without damaging the inner glycosidic bond.…”
Section: Introductionmentioning
confidence: 99%